Multilateral Safety Nets for Financial Crises - Eduardo Fernandez-Arias (Inter-American Development Bank (IDB), 2010)
There is an increasing need for a system of international lending of last resort (ILLR) to provide a safety net in the event of financial crises in vulnerable countries as financial globalization deepens and spreads. Multilateral progress to address liquidity and solvency crises has been patchy and inconsistent, with no clear distinction between the two; in particular, there is still no framework to address sovereign debt restructuring. This paper proposes an integrated system of specialized ILLR facilities to address problems of liquidity, adjustment, and debt restructuring in a focused but robust way as crises evolve and morph, structured in tiers to cater to countries capacity to prequalify for automatic support. It further proposes feasible legal reform to subject creditors to standstills and seniority dilution as in domestic bankruptcy in order to empower ILLR to facilitate orderly workouts in debt restructuring. Multilateral development banks would play important supporting roles.
Keywords: F34; F53; F55; 330; Safety nets; lender of last resort; liquidity crisis; solvency crisis; sovereign debt restructuring